2020
DOI: 10.3390/agronomy10091418
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Term Influence of Organic Fertilization on the Quality and Yield of a Celery Crop

Abstract: For some years now, part of society has been demanding the implementation of circular economy models and so the use of organic matter as a source of nutrients is once again taking center stage. In this scenario, the aim of this work was to implement an integrated management model for a farm and to study the influence on a celery crop of organic amendments (animal and vegetable) obtained on the farm, as opposed to inorganic fertilization. This influence was evaluated for the yield and the nutritional, organolep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Zapata et al ( 2013 ) reported that hue angle decreased progressively during broccoli storage, and the final hue angle in conventional broccoli was significantly lower than in organic broccoli. Navarro et al ( 2020 ) also found the highest L * values in organic treatments compared to inorganic ones.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Zapata et al ( 2013 ) reported that hue angle decreased progressively during broccoli storage, and the final hue angle in conventional broccoli was significantly lower than in organic broccoli. Navarro et al ( 2020 ) also found the highest L * values in organic treatments compared to inorganic ones.…”
Section: Discussionmentioning
confidence: 84%
“…chroma value in the organic treatments may be due to accelerated maturation compared to the chemical treatments. Similarly,Navarro et al (2020) reported that the chroma value in the organic fertilizer treatments was higher compared to the control. The organic fertilizer treatments delayed celery color changes the most (reduction in hue angle).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Navarro et al [29] discovered that the yield and size of marketable organs in celery plants were greater with inorganic fertilizer treatment; however, the nutritional quality of the celery plants was better in those plants treated with organic fertilizer. Tanwar et al [30] also reported that biological amendments increased celery yield by increasing leafstalk length, the number of leafstalks, leaf area, and basal disc diameter.…”
Section: Yield Components In Celerymentioning
confidence: 99%
“…For example, when the photoperiod exceeded 12 h, the yield of dandelion increased, and the accumulation of antioxidant metabolites in stevia rebaudiana gradually rose [14,15]. In cruciferous plants, it was found that there was no significant difference in polyphenol and flavonoid content between different photoperiods (12,14,16,18, and 20 h) treatments for kale, and the total mustard oil content was the lowest in cabbage with a 12 h photoperiod and Chinese kale with a 16 h photoperiod [16].…”
Section: Introductionmentioning
confidence: 98%